Bioaccumulation of mercury in fish and risk of ingestion in an indigenous community in the Peruvian Amazonia - Panduro, Grober (2020)
Mercury (Hg) is a toxic heavy metal that causes damage to the central nervous system, alters human behavior, and has an impact on aquatic biota. The aim of this study was to evaluate the bioaccumulation by Hg in fish and the risk for ingestion in an indigenous community (IC) in the Peruvian Amazonia during the dry and rainy season. The community Santa Rosa de Tamaya y Tipishca is located in the lower basin of the Abujao River. The study was carried out with 119 inhabitants grouped into 22 families, with average ages of 9 and 38 years for children and adults, respectively. The fish were collected using mainly trawl nets and were identified following the standard taxonomic morphological procedure. The Hg content in fish muscle was done using atomic fluorescence spectrometry. The results show that the four most consumed fish species by the NC were Pterygoplichthys pardalis (Castelnau, 1855) "Amazon sailfin catfish" (Loricariidae), Prochilodus nigricans Spix and Agassiz, 1829 " Black prochilodus" (Prochilodontidae), Pseudoplatystoma punctifer (Castelnau, 1855) "Spotted Tigerr Shovelnose catfish" (Pimelodidae) and Calophysus macropterus (Lichtenstein, 1819) " Zamurito" (Pimelodidae). The level of exposure was extremely high and the danger was medium. The maximum allowable dose of methylmercury (MeHg) per week according to WHO is 1.6 μg MeHg/kg/week. This limit was exceeded by C. macropterus for NC children. It is concluded that the health risk of the population of the CN of the Peruvian Amazon by MeHg is high.